Development and Evaluation of an Δ aroA / Δ htrA Salmonella enteritidis Vector Expressing Eimeria maxima TRAP Family Protein EmTFP250 with CD 154 (CD 40L) as Candidate Vaccines against Coccidiosis in Broilers - Shivaramaiah, S.; Barta, J.R.; Layton, S.L.; Lester, C.; Kwon, Y.M.; Berghman, L.R.; Hargis, B.M.; Tellez , G. (International Journal of Poultry Science, 2010)
Coccidiosis is caused by parasites of the genus Eimeria, belonging to phylum Apicomplexa. EmTFP250 is a high molecular mass, asexual stage antigen from Eimeria maxima (EM) strongly associated with maternal immunity in newly hatched chickens. Cloning and sequence analysis predict the antigen to be a novel member of the Thrombospondin-Related Adhesive Protein (TRAP) family. Three novel attenuated Salmonella enteritidis strains (ΔSE) expressing TRAP oligopeptides in association with a potential immune-enhancing CD 154 sequence, on the outer membrane protein lamB, were developed. Broiler chicks were grouped based on treatment and 108 cfu/chick of vectors expressing one of three sequences, or vehicle alone, was orally administered to each group. At 21 d of age, all groups were challenged with 104 sporulated oocysts/chick orally. Mortality at 5d post-challenge was markedly different (p